Automating Production Process Data Acquisition Towards Spaghetti Chart 4.0 - Al-Zubaidi, Salam Qaddoori Dawood; Coli, Elena; Fantoni, Gualtiero (International Journal of Industrial Engineering and Management, 2022)
Automation of logistics and production processes is one of the significant goals of the Industry 4.0 movement. Thus, this study uses the automatic data acquisition approach to automatically create Spaghetti Charts (SC), decrease the required time spent on collecting data, and provide a fast analysis (feedback). Smartphone technology used for drawing the automated spaghetti diagram has potential drawbacks related to safety, security, the privacy of organizations, and independency. So, Method Time Measurement 4.0 and RStudio software are used to collect the real data and draw the spaghetti chart, respectively, as an alternative solution. The experiment results for four scenarios (different Facility layouts and processes) prove that the approach is competitive, with cycle time reduction exceeding 40% less than the conventional facility layout and process plan. The proposed solution of the wearable device is promising for replacing smartphone technology with smart spaghetti chart systems. Article history: Received (November 29, 2021); Revised (May 18, 2022); Accepted (May 25, 2022); Published online (June 15, 2022)